Resveratrol and its derivates improve inflammatory bowel disease by targeting gut microbiota and inflammatory signaling pathways - Ming Li; Ping Li; Rongxue Tang; Hui Lu (Food Science and Human Wellness)
Inflammatory bowel disease (IBD) is a chronic inflammatory lesion of the intestine, mainly manifested by infiltration of intestinal inflammatory cells and imbalance of gut microbiota. Conventional treatments for IBD include antibiotics, immunosuppressive agents, 5-aminosalicylic acid, steroids and surgery, which have high toxic side effects. Resveratrol is a natural polyphenol, and its various derivatives have anti-oxidation and anti-inflammatory properties. In this paper, we comprehensively review the mechanism of resveratrol and its derivates to alleviate IBD by improving intestinal barrier, regulating the unbalanced gut microbiota, and targeting various inflammatory signaling pathways.